EDUCATIONAL SEMINAR “RECOVERING AND GROWING FROM MISTAKES” TO INCREASING THE RESILIENCE OF WARGA BINAAN PEMASYARAKATAN (CORRECTIONAL INMATES) IN RUTAN KELAS I MAKASSAR - Nabila Putri Anwar; Nabilah Assakinah BP; Nabila Ikram; Muhammad Faiz Muttaqi Sukri; Basti Tetteng; Maya Annisa Mursal (Universitas 45 Surabaya, 2022)
Abstract: Kuliah Kerja Profesi (KKP) is an academic student activity carried out in an agency, institution, or company in accordance with the field of student education. The program was carried out at Rutan Kelas I Makassar. Correctional inmates experienced several psychological and emotional problems while being detained such as anxiety, trouble sleeping, sad, depressed, bored, lonely and still thinking the mistakes they had made. Correctional inmates were given intervention in the form of an educational seminar entitled “Recovering and Growing from Mistakes” and raising the theme of Resilience. The purpose of the educational seminar activity is to increase the resilience of correctional Inmates so that they don’t continue to suffer from past mistakes and are able to rise again. This program uses a quasi-experimental with a one-group-pretest-posttest design approach. The result of this educational seminar program is that the knowledge of the correctional inmates’s resilience after being given treatment has increased.